Synchronization and Stability of Elasticity Coupling Two Homodromy Rotors in a Vibration System - Yongjun Hou; Mingjun Du; Pan Fang; Yuwen Wang; Liping Zhang (Shock and Vibration)
The mechanical model of an elasticity coupling 1-DOF system is proposed to implement synchronization; the simplified model is composed of a rigid body, two induction motors, and a connecting spring. Based on the Lagrange equations, the dynamic equation of the system is established. Moreover, a typical analysis method, the Poincare method, is applied to study the synchronization characteristics, and the balanced equations and stability criterion of the system are obtained. Obviously, it can be seen that many parameters affect the synchronous state of the system, especially the stiffness of the support spring, the stiffness of the connecting spring, and the installation location of the motors. Meanwhile, choose a suitable stiffness of the connecting spring (k), which would play a significant role in engineering. Finally, computer simulations are used to verify the correctness of the theoretical analysis.